Development of Green and High Throughput Microplate Reader-Assisted Universal Microwell Spectrophotometric Assay for Direct Determination of Tyrosine Kinase Inhibitors in Their Pharmaceutical Formulations Irrespective the Diversity of Their Chemical Structures - Ibrahim A. Darwish; Nourah Z. Alzoman (Molecules, 2023)
This study discusses the development and validation of a universal microwell spectrophotometric assay for TKIs, regardless of the diversity in their chemical structures. The assay depends on directly measuring the native ultraviolet light (UV) absorption of TKIs. The assay was carried out using UV-transparent 96-microwell plates and the absorbance signals were measured by a microplate reader at 230 nm, at which all TKIs had light absorption. Beer’s law correlating the absorbances of TKIs with their corresponding concentrations was obeyed in the range of 2–160 µg mL–1 with excellent correlation coefficients (0.9991–0.9997). The limits of detection and limits quantitation were in the ranges of 0.56–5.21 and 1.69–15.78 µg mL–1, respectively. The proposed assay showed high precision as the values of the relative standard deviations for the intra- and inter-assay precisions did not exceed 2.03 and 2.14%, respectively. The accuracy of the assay was proven as the recovery values were in the range of 97.8–102.9% (±0.8–2.4%). The proposed assay was successfully applied to the quantitation of all TKIs in their pharmaceutical formulations (tablets) with reliable results in terms of high accuracy and precision. The assay greenness was evaluated, and the results proved that the assay fulfils the requirements of green analytical approach. The proposed assay is the first assay that can analyse all TKIs on a single assay system without chemical derivatization or modifications in the detection wavelength. In addition, the simple and simultaneous handling of a large number of samples as a batch using micro-volumes of samples gave the assay the advantage of high throughput analysis, which is a serious demand in the pharmaceutical industry.